A Direct Electrochemical Detection Method of Melanoma Based on Melanoma Biomarker. Issue 8 (9th July 2014) - Mossberg, Michal; Vernick, Sefi; Ortenberg, Rona; Markel, Gal; Diamand, Yosi Shacham‐; Rishpon, Judith
Abstract A new method of detecting and diagnosing melanoma based on melanoma biomarker was developed and its feasibility demonstrated. The method is based on an electrochemical biosensor platform comprised of a special biochip and device, performing a multi‐channel amperometric detection of the enzymatic activity of tyrosinase, an enzyme biomarker of melanoma. The newly developed biosensor platform is able to electrochemically detect tyrosinase activity in fresh biopsy samples. This bioelectrochemical detection method is rapid, yielding results within minutes from biopsy removal. Using "as is" biopsy samples, without pretreatment, simplifies the process, saves time and reduces cost and labor dramatically. Using modern portable microelectronics provides an accurate biomarker expression measurement at the "point of care" increasing the accessibility of new bio‐chip technologies to the public.